Conduction mechanism of Co-doped ZnO transparent memristive devices. Issue 1 (February 2021) - Simanjuntak, Firman Mangasa; Chandrasekaran, Sridhar; Prasad, Om Kumar; Gapsari, Femiana; Prodromakis, Themis; Tseng, Tseung-Yuen
Abstract: The Co dopant substitutes the Zn atomic position in the hexagonal crystal lattice and generates acceptor defects. These defects play significant role in modulating the conduction mechanism of the memristive device. The devices without Co dopant have high concentration of donor defects so that the electron can flow easily through hopping these donor defects; henceforth, only weak filaments can be formed during the set process. Meanwhile, the increase of the acceptor defects in the films enhances the film resistivity. This acceptor defects also contribute to an increase of barrier height at the electrode/dielectric interface where the electrons require higher energy to overcome this barrier and, eventually, induce the formation of strong filaments during the set process.